SEJARAH PARADIGMA PENGUASAAN NEGARA TERHADAP BAHAN TAMBANG BATUBARA DAN HUBUNGANNYA DENGAN PERLINDUNGAN HAK-HAK EKONOMI RAKYAT - Chandra, Janto (Nurani, 2016)
Indonesia rich the natural resources, such the coal mineral deposits. But in the fact state control of the coal mine is more substance for investment purposes. The economic rights of the people have not been accommodated. There is still often conflicting relating to land by the public. From the historical arrangements control of natural resources since the Dutch era was indeed the economic factor of investment into primary interest and not for the people prosperity that result in people's economic rights unprotected. This article focused on the analysis of the historical of the paradigm of state control of the coal mines material connected to the protection of economic rights of the people. ملخص: اندونيسيا الغنية بالموارد الطبيعية، مثل الرواسب المعدنية الفحم. ولكن في سيطرة الدولة حقيقة منجم للفحم هو أكثر مادة لأغراض الاستثمار. لم يتم استيعاب الحقوق الاقتصادية للشعب. لا يزال هناك كثير من الأحيان متضاربة فيما يتعلق بالأرض من قبل الجمهور. من سيطرة الترتيبات التاريخية للموارد الطبيعية بما أن عصر الهولندي في الواقع العامل الاقتصادي من الاستثمار في المصلحة الأساسية وليس من اجل ازدهار الشعب التي تؤدي إلى حقوق الناس الاقتصادية غير المحمية. وركزت هذه المادة على تحليل تاريخي للنموذج من سيطرة الدولة على المواد مناجم الفحم متصلا حماية الحقوق الاقتصادية للشعب.